The Impact of Self-Advocacy Small-Group Instruction on the Ability of College Students With High-Incidence Disabilities to Request and Negotiate Accommodations. - Chambers, Alex W.; Holzberg, Debra G. (Journal of Applied Rehabilitation Counseling, 2025)
For students with specific learning disabilities (SLD) and/or attention-deficit/hyperactivity disorder (ADHD), the transition from secondary to postsecondary education presents significant challenges in acquiring and utilizing academic accommodations. Self-advocacy skills are essential for successfully navigating these educational environments. Rehabilitation counselors are in a unique position to provide supports such as self-advocacy instruction to improve postsecondary outcomes for their clients. This study investigated the impact of self-advocacy and conflict resolution (SACR) instruction, taught in a small-group setting, on the ability of three college students with SLD and/or ADHD to request and negotiate academic accommodations. Using a single-subject, multiple-probe, A = baseline, B = intervention, and C = generalization/maintenance (ABC) design, findings indicated an increase in level and trend between SACR instruction and students' improved accommodation requests during role-play and generalization conditions with a percentage of nonoverlapping data of 100% (p =.0025) for all participants. Social validity data indicated that participants found that the intervention helped them explain their needs, better understand their disabilities, and value the small-group format. Implications for rehabilitation counselors supporting postsecondary transitions and providing pre-enrollment preparation services are discussed, along with practical implementation strategies in vocational rehabilitation settings. Limitations and suggestions for future research are also discussed.